Heterogeneity in price elasticity of vehicle kilometers traveled: Evidence from micro-level panel data - Ivan Tilov; Sylvain Weber (University of Neuchâtel, Institute of Economic Research (IRENE), 2020)
This article presents an empirical estimation of the effect of fuel prices on vehicle kilometers traveled (VKT) using a panel dataset of 1,138 Swiss households. Elasticities are estimated for different segments of households, based on their socio-demographic and vehicle characteristics, as well as on their driving intensity. Our results indicate larger price elasticities than previous estimates based on aggregate data for Switzerland and reveal important heterogeneity in price sensitivity across segments. Households who live in urban areas, who live farther from their workplace, and who own more efficient vehicles are significantly more reactive to price variations. The results of a quantile regression model for panel data show that travel-intensive households are responsive to changes in gasoline price, while less intensive drivers do not exhibit statistically significant price elasticities. In addition to gasoline taxes, it therefore appears that non-price measures tailored to household segments would be useful to provide supplementary incentives to reduce distance traveled and/or avoid penalizing some specific groups.
Keywords: Q40; Q41; D12; R41; C21; 330; vehicle kilometers traveled (VKT); car-travel demand; fuel price; elasticities; household behavior; heterogeneity; quantile regression; panel data; Switzerland